Answer:
The solution to the given system of equation is;
![\begin{gathered} x=2 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pqoiggr2xyki9yb7cmhom2l376jbj9ux8k.png)
Step-by-step explanation:
Given the system of equation:
![\begin{gathered} x=7-y\text{ -----1} \\ x=-2y+12\text{ ----2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mv7rq4jqju3hkbn9rtwfpdads3sdrvpn59.png)
Let us make y the subject of formula in equation 1;
![\begin{gathered} x=7-y \\ y=7-x\text{ ----3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/539fk9kh4cv8h0irf5anvy9q6yjmocbjoq.png)
Let us substitute equation 3 into equation 2 and solve;
![\begin{gathered} x=-2y+12 \\ x=-2(7-x)+12 \\ x=-14+2x+12 \\ x=-14+12+2x \\ x=-2+2x \\ \text{collect the like terms;} \\ 2=2x-x \\ 2=x \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vwf34cexgsxx9uxt4cm3ccxeaja8gwh913.png)
We can now substitute to get y;
using equation 3;
![\begin{gathered} y=7-x \\ y=7-2 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jk1zy3rdpmfek4lsbm1gafdac2ufmvqflr.png)
Therefore, the solution to the given system of equation is;
![\begin{gathered} x=2 \\ y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pqoiggr2xyki9yb7cmhom2l376jbj9ux8k.png)